Fairy ponies: the midnight escape - Davidson, Zanna; Costa, Jana (Usborne Publishing Ltd : [distributor] HarperCollins Distribution Services : [distributor] HarperCollins Publishers Pty Ltd : [distributor] HarperCollins New Zealand : [distributor] Wild Dog Press London, 2010)
Holly is staying with her Great Aunt May when she discovers a tiny pony with shimmering wings. At first, she thinks she must be dreaming, until two fairy ponies visit her one night on an urgent undertaking: Puck the fairy pony has been snatched by the spoiled girl next-door, and the ponies need Holly's help to rescue him.